TLR-mediated activation of peripheral blood monocyte phagocytosis in patients with multiple sclerosis - A. I. Skliar; O. М. Koliada; N. І. Vdovichenko; T. I. Koliada (Patologìâ)
The aim of the study: to reveal peculiarities of the phagocytic activity of TLR4, TLR7/8-activated monocytes of peripheral blood, depending on the type of multiple sclerosis and clinical effectiveness of the treatment.